How to Teach Introduction to Philosophy? - Berčić, Boran (Od filozofije poučevanja do poučevanja filozofije: Festschrift Rudi Kotnik, 2025)
The concern that teaching philosophy differs from doing philosophy is valid. In continental European high schools, philosophy is often taught as a historical narrative from pre-Socratics to Sartre or Heidegger, emphasizing cultural and historical facts over philosophical inquiry. This method can reduce philosophy to anecdotes about famous philosophers, neglecting clear theories and arguments. Consequently, teaching philosophy becomes detached from doing philosophy. Two main issues arise: it misrepresents philosophy and fails to prepare students for essay writing. In this paper, I argue that students are not ready to write a philosophical essay before the third year of university study in philosophy; they should focus on writing one-page summaries of theories and arguments. Thus, grading high school essays is ineffective. But they could all be taught – classical philosophical positions and arguments. I am summarizing 17 points, or guidelines, that may be useful for the future teachers of introductory courses.